Effects of sacubitril-valsartan on heart failure patients with mid-range ejection fractions: A systematic review and meta-analysis - Qin, Jianbin; Wang, Weijian; Wei, Ping; Huang, Ping; Lin, Ruizhen; Yue, Jinming (Frontiers in Pharmacology, 2022)
Aim: The effect of sacubitril-valsartan (ARNI) in heart failure (HF) patients with mid-range ejection fractions (HFmrEF) remains unclear. This study aimed to investigate the effects of ARNI in HFmrEF patients. Methods: From inception to 15 February 2022, articles were searched via PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure, Whip, and Wanfang databases. Left ventricular functions, indicators related to HF, quality of life score, 6-Minute Walk Test, total effective rate, mortality, readmission rate, and adverse events were the outcomes. Relative risk (RR), weighted mean difference (WMD), and 95% confidence interval (CI) were used to evaluate the outcomes. The heterogeneity test was conducted for each indicator and measured by I2 statistics. Subgroup analysis was performed regarding the type of study and duration of treatment. Results: Sixteen studies involving 1,937 patients were included in this study. Our results showed ARNI was likely to improve left ventricular function by increasing the left ventricular ejection fraction (LVEF) (WMD: 2.36, 95%CI: 1.09 to 3.62), stroke volume (WMD: 16.800, 95%CI: 11.385 to 22.215), and left ventricular short-axis shortening rate (WMD: 2.05, 95%CI: 0.25 to 3.86), decreasing left ventricular end-diastolic dimension (WMD: -2.48, 95%CI: -3.83 to -1.13), left atrial diameter (WMD: -2.23, 95%CI: -2.83 to -1.63), C-reactive protein level (WMD: -1.40, 95%CI: -2.62 to -0.18), and N-terminal-pro B-type natriuretic peptide level (WMD: -494.92, 95%CI: -641.34 to -348.50). ARNI has a higher total effective rate (RR: 1.15, 95%CI: 1.08 to 1.21), Kansas City cardiomyopathy questionnaire (WMD: 4.13, 95%CI: 3.46 to 4.81), and 6-Minute Walk Test (WMD: 51.35, 95%CI: 26.99 to 75.71) compared with angiotensin-converting enzyme inhibitors (ACEI) and angiotensin receptor blockers (ARB). In addition, ARNI decreased the readmission rate (RR: 0.54, 95%CI: 0.43 to 0.68) (all P<0.05). Nevertheless, there were no significant differences in the adverse outcomes. Conclusion: This meta-analysis suggests ARNI may be an effective strategy with which to improve the left ventricular function, and quality of life, and reduce the readmission rate in HFmrEF patients. However, long-term clinical studies with large samples are still needed to further explore the efficacy and safety of ARNI compared with ACEI or ARB in the HFmrEF population.